Antioxidant flavonol glycosides from Nectandra grandiflora (Lauraceae) - Ribeiro, Alan Bezerra; Silva, Dulce Helena Siqueira; Bolzani, Vanderlan da Silva (Eclética Química, 2002)
The bioassay-guided fractionation of the ethanol extract from Nectandra grandiflora leaves led to the isolation of two flavonol glycosides which inhibited the bleaching of b -carotene on the TLC assay. Both compounds had their molecular structures elucidated by means of extensive use of uni- and bidimensional NMR techniques and were identified as 3-O-b -rhamnosylkaempferol and 3-O-b -rhamnosylquercetine.